Is Duplex-Ultrasound a useful tool in defining rejection episodes in composite tissue allograft transplants? - Loizides, Alexander; Kronberger, Irmgard-Elisabeth; Plaikner, Michaela; Gruber, Hannes (Medical ultrasonography, 2015)
Immunologic reactions in transplanted organs are in more or less all allograft patients detectable: clear parameters exist as e.g. in renal transplants where the clearance power reduces by rejection. On the contrary, in composite tissue allografts clear and objective indicators stating a rejection episode lack. We present the case of a hand-transplanted subject with signs of acute transplant rejection diagnosed by means of Duplex Ultrasound and confirmed by biopsy.